2020
DOI: 10.1007/978-3-030-64559-5_43
|View full text |Cite
|
Sign up to set email alerts
|

Interface Design for HCI Classroom: From Learners’ Perspective

Abstract: Having a good Human-Computer Interaction (HCI) design is challenging. Previous works have contributed significantly to fostering HCI, including design principle with report study from the instructor view. The questions of how and to what extent students perceive the design principles are still left open. To answer this question, this paper conducts a study of HCI adoption in the classroom. The studio-based learning method was adapted to teach 83 graduate and undergraduate students in 16 weeks long with four ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Several studies [51]- [53] have shown that technology, especially artificial intelligence (AI), can help maintain academic integrity through tools like Grammarly, Turnitin, and White Smoke that check for plagiarism, proctor students, and keep an eye on how they act online. Other studies [54], [55] talked about gamification, which uses AI for educational purposes and significantly impacts instruction quality. Gamification is also a part of or uses virtual reality and 3-D technologies differently.…”
Section: Roles Of Teachersmentioning
confidence: 99%
“…Several studies [51]- [53] have shown that technology, especially artificial intelligence (AI), can help maintain academic integrity through tools like Grammarly, Turnitin, and White Smoke that check for plagiarism, proctor students, and keep an eye on how they act online. Other studies [54], [55] talked about gamification, which uses AI for educational purposes and significantly impacts instruction quality. Gamification is also a part of or uses virtual reality and 3-D technologies differently.…”
Section: Roles Of Teachersmentioning
confidence: 99%
“…Exploring these questions can lead to meaningful pedagogical insights for the CSCW community. Designing through group collaboration is also a learning process, because students generate ideas, discuss, critique, prototype, communicate with each other, and implement the final prototypes throughout an iterative design process [6,10]. While previous research emphasizes the significance of collaboration in design education, such as brainstorming leading to effective design outcomes [11] and collaborative context fostering participatory culture [12], several challenges regarding online collaboration have been raised.…”
Section: Introductionmentioning
confidence: 99%